Effect of Thyroxine Hormone by Oral on Growth and Survival Rate of Coral Platy Xiphophorus maculates - M. Zairin Junior; R.G. Pahlawan; M. Raswin (Jurnal Akuakultur Indonesia)
Thyroxine is known as a hormone that can affect growth of fish by increasing the metabolic rate, feed efficiency and protein retention.  In this study, effect of thyroxine administration through feed on growth and survival of coral platy fish (Xiphophorus maculatus) was observed.  Dosage of thyroxine used was 0.2, 2 and 20 mg/kg of feed, and were combined with duration time of treatment i.e. 1, 2 and 3 weeks.  All treatments were performed triplicate.  The results of study show that higher growth in length (21.3 mm) and weight (244.5 mg) was obtained by administration of 20 mg thyroxine per kilogram of feed for two weeks and this treatment had no effect on the survival rate of coral platy fish